Elimination of Schistosoma mansoni Adult Worms by Rhesus Macaques: Basis for a Therapeutic Vaccine? - R Alan Wilson; Jan A M Langermans; Govert J van Dam; Richard A Vervenne; Stephanie L Hall; William C Borges; Gary P Dillon; Alan W Thomas; Patricia S Coulson (Public Library of Science (PLoS), 2008)
Among animal models of schistosomiasis, the rhesus macaque is unique in that an infection establishes but egg excretion rapidly diminishes, potentially due to loss of adult worms from the portal system via shunts or death by immune attack.To investigate this, six rhesus macaques were exposed to Schistosoma mansoni cercariae and the infection monitored until portal perfusion at 18 weeks. Despite a wide variation in worm numbers recovered, fecal egg output and circulating antigen levels indicated that a substantial population had established in all animals. Half the macaques had portal hypertension but only one had portacaval shunts, ruling out translocation to the lungs as the reason for loss of adult burden. Many worms had a shrunken and pallid appearance, with degenerative changes in intestines and reproductive organs. Tegument, gut epithelia and muscles appeared cytologically intact but the parenchyma was virtually devoid of content. An early and intense IgG production correlated with low worm burden at perfusion, and blood-feeding worms cultured in the presence of serum from these animals had stunted growth. Using immunoproteomics, gut digestive enzymes, tegument surface hydrolases and antioxidant enzymes were identified as targets of IgG in the high responder animals.It appears that worms starve to death after cessation of blood feeding, as a result of antibody-mediated processes. We suggest that proteins in the three categories above, formulated to trigger the appropriate mechanisms operating in rhesus macaques, would have both prophylactic and therapeutic potential as a human vaccine.